The legislation, search, recovery, identification and repatriation of conflict casualties worldwide: Introducing the WWI and WWII Special Issue - Márquez-Grant, Nicholas; Errickson, David (Elsevier, 2021)
Conflict casualties refer to those individuals who are lost due to military conflict or war. The involvement of forensic archaeologists and anthropologists in the legal search, recovery, documentation, identification, and repatriation/reburial of conflict casualties is well known. Internationally, there are a number of professional organisations who ethically recover and identify these individuals. However, at the same time, some organisations and individuals have raised significant concerns about working in other countries, understanding specific laws and protocols, and how the whole recovery and identification process should be undertaken. Through this special issue, Forensic Science International is interested in promoting these investigative good-practice procedures, illustrated with case studies, and ethical and legal considerations when undertaking and disseminating these humanitarian missions to the wider forensic community. This Special Issue focuses primarily on the First and Second World Wars, yet other conflicts are covered, and includes the views and perspectives from different organisations within specific countries in the format of original papers, commentaries, and case reports. Specifically, these papers include the legislative regulations, information regarding the authorities to be consulted on and who deal with human remains, the organisations and professionals who are involved with the recovery and analysis of human remains, the process of identification, and how this information is disseminated to the public.
Keywords: legislation; human remains; forensic archaeology; forensic anthropology; Second World War; First World War